2022
DOI: 10.1126/science.abm0811
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous infection and vaccination shapes immunity against SARS-CoV-2 variants

Abstract: Immune imprinting For severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), immune responses to heterologous variants are influenced by a person’s infection history. Healthcare workers (HCWs) may be exposed to several doses and types of antigens, either by natural infection or by vaccination. Reynolds et al . studied a cohort of UK HCWs followed since March 2020. The immunological profiles of these people depended on how often the subject had encountered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
106
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 42 publications
15
106
1
Order By: Relevance
“…Following antigenic stimulation with the spike-derived peptides, a predominant IFNg response was observed in all the examined individuals, ranging from 50 to 400 secreting cells per 10 6 PBMC, and a lower IL-10 response, ranging from 15 to 82 cells per 10 6 PBMC (Figure 1 and Figure S1). The experimental setup included a 48 h antigen stimulation step to allow manifestation of the reactivity of IL-4-expressing T cell clones potentially present in the samples; however, almost undetectable levels of IL-4 reactivity were determined, in accordance with previous data pertaining to the responses elicited by the BNT162b2 and m1273 vaccines [2,4,[8][9][10][11][12][13]. A comparison of the average response to the wild-type and Omicron spike (Figure 2) indicated only a slight nonsignificant decrease from 201 IFNg-secreting cells following activation with the wild-type spike, to 188 cells responding to the Omicron spike.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Following antigenic stimulation with the spike-derived peptides, a predominant IFNg response was observed in all the examined individuals, ranging from 50 to 400 secreting cells per 10 6 PBMC, and a lower IL-10 response, ranging from 15 to 82 cells per 10 6 PBMC (Figure 1 and Figure S1). The experimental setup included a 48 h antigen stimulation step to allow manifestation of the reactivity of IL-4-expressing T cell clones potentially present in the samples; however, almost undetectable levels of IL-4 reactivity were determined, in accordance with previous data pertaining to the responses elicited by the BNT162b2 and m1273 vaccines [2,4,[8][9][10][11][12][13]. A comparison of the average response to the wild-type and Omicron spike (Figure 2) indicated only a slight nonsignificant decrease from 201 IFNg-secreting cells following activation with the wild-type spike, to 188 cells responding to the Omicron spike.…”
Section: Resultssupporting
confidence: 58%
“…Accordingly, for several emerging VOCs, it was shown that a lower neutralizing antibody response was correlated with lower efficiency of the vaccine and higher levels of immune breakthrough infections [4,5]. Considering the antibody titer kinetics following vaccination and their potential waning below the neutralizing levels, it is essential to maintain protective T cell memory responses, which are expected to exhibit significant longevity [6][7][8]. Immune escape from the humoral response is mostly a result of specific mutations of a given antigen, which occur in a convergent microevolutionary process and therefore affect equally different individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Following antigenic stimulation with the spike-derived peptides, a predominant IFNg response was observed in all the examined individuals, ranging from 50 to 400 secreting cells per 10 6 PBMC, and a lower IL-10 response, ranging from 15 to 82 cells per 10 6 PBMC (figure 1 and 1S). The experimental setup included a 48 hours antigen stimulation step, to allow manifestation of reactivity of IL-4-expressing T cell clones potentially present in the samples, however, almost undetectable levels of IL-4 reactivity was determined, in accordance with previous data pertaining to the responses elicited by the BNT162b2 and m1273 vaccines [2,4,813]. Comparison of the average response to the wild type and Omicron spike (Figure 2), indicated only a slight, non-significant decrease, from 201 IFNg-secreting cells following activation with the wild type spike, to 188 cells responding to the Omicron spike.…”
Section: Resultsmentioning
confidence: 60%
“…Accordingly, for several emerging VOCs, it was shown that a lower neutralizing antibody response is correlated with lower efficiency of the vaccine and higher levels of immune-breakthrough infections [4,5]. Considering the antibody titer kinetics following vaccination and their potential waning below the neutralizing levels, it is essential to maintain protective T cell memory responses, which are expected to exhibit significant longevity [6][7][8]. Immune escape from humoral response is mostly a result of specific mutations of a given antigen, which occur in a convergent microevolutionary process and therefore affects equally different individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The initial exposure to a pathogen will prime a specific immune response and subsequent exposures are impacted by this pre-existing immunity including B cells and T cells specific to the original strain. This phenomenon, known as “original antigenic sin” or “antigenic imprinting” is commonly observed in the influenza field and may have a role to play in coronavirus biology 31 , 32 , 33 , 34 (32 preprint). As priming of the immune response against the original wild-type spike protein may impact the ability to switch specificity of the response to the Beta VoC (B.1.351), we measured antibody and T cell responses after one or two doses of the original ChAdOx1 nCoV-19 vaccine (AZD1222) followed by a single dose of AZD2816.…”
Section: Discussionmentioning
confidence: 99%